1998
DOI: 10.1084/jem.188.5.845
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Mycobacterium bovis Bacillus Calmette-Guérin Secreting Merozoite Surface Protein 1 (MSP1) Induces Protection against Rodent Malaria Parasite Infection Depending on MSP1-stimulated Interferon γ and Parasite-specific Antibodies

Abstract: The merozoite surface protein 1 (MSP1) has emerged as a leading malaria vaccine candidate at the erythrocytic stage. Recombinant bacillus Calmette-Guérin (rBCG), which expressed a COOH-terminal 15-kD fragment of MSP1 of Plasmodium yoelii (MSP1-15) as a fusion protein with a secretory protein of Mycobacterium kansasii, was constructed. Immunization of mice with this rBCG induced a higher degree of protection against blood-stage parasite infection than with recombinant MSP1-15 in the RIBI adjuvant (RIBI ImmunoCh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(38 citation statements)
references
References 65 publications
0
38
0
Order By: Relevance
“…Finally, we analyzed immune responses in PyL-infected TLR9 Ϫ/Ϫ mice. CD4 ϩ T cells and their product IFN-␥ are known to be important for protection against blood-stage malaria (34,35). Flow cytometric analyses revealed that infection of TLR9 Ϫ/Ϫ mice with PyL increased activated (CD62L low , CD69 high ) and IFN-␥ ϩ populations among splenic CD4 ϩ T cells, compared with infection of WT mice (Fig.…”
Section: Infection With Pyl Failed To Activate Tregs In Tlr9 ϫ/ϫ Micementioning
confidence: 99%
“…Finally, we analyzed immune responses in PyL-infected TLR9 Ϫ/Ϫ mice. CD4 ϩ T cells and their product IFN-␥ are known to be important for protection against blood-stage malaria (34,35). Flow cytometric analyses revealed that infection of TLR9 Ϫ/Ϫ mice with PyL increased activated (CD62L low , CD69 high ) and IFN-␥ ϩ populations among splenic CD4 ϩ T cells, compared with infection of WT mice (Fig.…”
Section: Infection With Pyl Failed To Activate Tregs In Tlr9 ϫ/ϫ Micementioning
confidence: 99%
“…34 This protein is responsible for protective immunity against malaria infection, 35,36 and is one of the most promising malaria vaccine candidates. 29,37,38 We have previously described antibodies produced against the rBCG vaccine inhibited P. falciparum 3D7 merozoite invasion of red blood cells in vitro. 33 Moreover, the rBCG strain also stimulated higher cellular and humoral immune responses in animal model.…”
Section: Introductionmentioning
confidence: 99%
“…Mycobacterium bovis bacille Calmette-Guérin (BCG), the only vaccine currently available for the prevention of tuberculosis, is among the most extensively used vector for developing recombinant vaccines for other diseases, including malaria. [29][30][31] Using this strategy, our group previously cloned and expressed a synthetic gene encoding the C-terminus of the merozoite surface protein-1 (MSP-1 19 ; referred in this study as MSP-1C) in a recombinant BCG (rBCG016; referred in this study as rBCG) construct. 32,33 MSP-1C is a 19 kDa blood-stage antigen produced by proteolysis of a high molecular weight precursor, 195 kDa MSP-1 protein.…”
Section: Introductionmentioning
confidence: 99%
“…Although immune responses against recombinant Ags were often generated in the mouse system, this does not always translate to humans. For example, vaccination with rBCG as Ag carrier produced Ag-specific Th1 response and protective serum Ab against Plasmodium yoelii in rodents (41). In a clinical trial involving human subjects, the intradermal administration of rBCG vector failed to stimulate Ab responses against delivered Ag (42).…”
Section: Discussionmentioning
confidence: 99%